THE ROLE OF SUPERVISORS IN SUPPORTING DIGITAL-BASED MADRASAHS IN FOSTERED MADRASAHS IN SOPPENG REGENCY - Harnis (Adisam Publisher, 2026)
The digital transformation in education necessitates active involvement from various stakeholders, including madrasah supervisors. Supervisors play a pivotal role in assisting digital-based madrasahs to ensure the effective and efficient implementation of technology. The application of Information Technology (IT) in education has emerged as an increasingly relevant and significant subject, particularly in madrasahs, which face the challenge of leveraging IT effectively. The digital era has created numerous opportunities across various sectors, including education. As Islamic educational institutions, madrasahs must adapt to these changes to remain relevant and effective in educating future generations. This adaptation aims to enhance the quality of education, improve learning effectiveness, and optimize madrasah management. This study aims to explore the role of supervisors in supporting digital-based madrasahs by utilizing IT within fostered madrasahs in Soppeng Regency. It also examines the challenges encountered and proposes strategies to optimize supervisory roles. A qualitative research method was employed, utilizing a case study approach involving several fostered madrasahs in Soppeng Regency. The findings reveal that supervisors hold a critical role in guiding, supporting, and evaluating the implementation of digital technology in madrasahs.